Pop Art : Prints & Multiples : Organized and circulated by the Art Gallery of Ontario, 1982-83. - Glenbow Museum, Calgary; Waterloo Art Gallery, Kitchener; Regional Art Gallery, London; Laurentian University Museum & Arts Centre, Sudbury; Rodman Hall Arts Centre, St.Catharines; The Art Gallery of Peterborough, Peterborough; Art Gallery of Ontario, Toronto (Toronto : Art Gallery of Ontario, 1982)
Blake, Peter ; Hamilton, Richard ; Jones, Alles ; Lichtenstein, Roy ; Oldenburg, Claes ; Rosenquist, James ; Warhol, Andy
Pop Art : Prints & Multiples, Glenbow Museum, Calgary, Mar. 13 - Apr. 25, 1982 / Waterloo Art Gallery, Kitchener, May 30 - June 27, 1982 / Regional Art Gallery, London, July 9 - Aug. 8, 1982 / Laurentian University Museum and Arts Centre, Sudbury, Sept. 14 - Oct. 3, 1982 / Rodman Hall Arts Centre, St. Catharines, Oct. 8 - 31, 1982 / The Art Gallery of Peterborough, Nov. 11 - Dec. 5, 1982 / Art Gallery of Ontario, Toronto, Dec. 18, 1982 - Feb. 6, 1983 / Art Gallery of Nova Scotia, Halifax, Mar. 4 - Apr. 3, 1983
boek